2021
DOI: 10.1371/journal.pone.0251546
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-sensitive outcomes in district nursing care: A Delphi study

Abstract: Objectives To determine nurse-sensitive outcomes in district nursing care for community-living older people. Nurse-sensitive outcomes are defined as patient outcomes that are relevant based on nurses’ scope and domain of practice and that are influenced by nursing inputs and interventions. Design A Delphi study following the RAND/UCLA Appropriateness Method with two rounds of data collection. Setting District nursing care in the community care setting in the Netherlands. Participants Experts with current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 14 publications
(34 reference statements)
0
31
0
Order By: Relevance
“…A strength of this study was the evaluation of quality of care using nursing‐sensitive outcomes (NSOs; Twigg et al, 2015 ). NSOs are not only relevant for the scope and domain of nursing practice (Veldhuizen et al, 2021 ) but could also be considered relevant for investigating the effects of family participation. Another strength of this study is the sample size of 530.…”
Section: Discussionmentioning
confidence: 99%
“…A strength of this study was the evaluation of quality of care using nursing‐sensitive outcomes (NSOs; Twigg et al, 2015 ). NSOs are not only relevant for the scope and domain of nursing practice (Veldhuizen et al, 2021 ) but could also be considered relevant for investigating the effects of family participation. Another strength of this study is the sample size of 530.…”
Section: Discussionmentioning
confidence: 99%
“…The musical background will be assessed as a possible explanation for the success of the live or recorded music interventions. Other complications (classified according to Clavien-Dindo [ 33 ], nursing-sensitive outcomes such as dehydration and falling [ 34 ]) will be explored for changes in the music groups compared to care-as-usual to derive hypotheses for future studies.…”
Section: Methodsmentioning
confidence: 99%
“…Other study parameters used in this study are as follows: (1) comorbidities (Charlson comorbidity index) [32]; (2) complications (Clavien Dindo [33] and nurse-sensitive outcomes [34]); (3) postoperative days (T0=surgery); (4) surgery characteristics (invasiveness, etc) [20]; (5) musical background (excerpt from DMBQ) [30]; (6) age; and (7) presurgery cognitive testing [22] (eg, 6-item cognitive impairment score) [28].…”
Section: Other Study Parametersmentioning
confidence: 99%
“…This is the first step to selecting appropriate solutions and facilitation to help district nursing care implement nurse‐sensitive outcomes. The following research questions guided this study: Which of the 26 nurse‐sensitive outcomes, previously identified by experts (Veldhuizen, van den Bulck, et al, 2021), are currently measured in Dutch district nursing practice, and how are these outcomes measured? How are nurse‐sensitive outcomes used to learn and improve current practice? What are the barriers and facilitators of using nurse‐sensitive outcomes in district nursing care? …”
Section: Introductionmentioning
confidence: 99%
“…A potential reason for this absence of evidence is the worldwide variation in the organisation, delivery and funding of district nursing care (Genet et al, 2012 ; Jarrín et al, 2019 ; Van Eenoo et al, 2016 ). A recent Delphi study was conducted to identify what nurse‐sensitive outcomes are relevant for district nursing care (Veldhuizen, van den Bulck, et al, 2021 ). The Delphi study identified 46 potentially nurse‐sensitive patient outcomes for district nursing care in the literature, of which 26 were assessed as nurse sensitive by various experts in district nursing care (Veldhuizen, van den Bulck, et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%